The resilience of the Biden administration's climate policy: On the danger of a climate policy u-turn under a second Trump presidency - Sonja Thielges (Stiftung Wissenschaft und Politik (SWP), 2024)
The United States will play a crucial role in global climate protection in what has been called the "super election year" of 2024. After three-and-a-half years of having scored huge successes in climate protection, President Joe Biden could be succeeded by Donald Trump in January 2025, according to opinion polls. Trump used his first Presidency (2017-2021) to largely reverse the climate protection measures of the previous administration; and he intends to take the same approach if he wins in November. Conservative think tanks have provided him with a detailed blueprint for doing so with the "Mandate for Leadership: The Conservative Promise". Trump's return to the White House would deal a fatal blow to climate protection. Many of the Biden administration's climate policy measures could be scrapped by a second Trump administration. While the future of US climate policy depends largely on the results of the elections to the White House and Congress, an important factor will also be the progress that has been made in the individual US states.
Keywords: 320; Joe Biden; Donald Trump; Kamala Harris; US climate policy; Priority Climate Action Plan (PCAP); Conservative Climate Caucus; Paris Agreement; decarbonization; Environmental Protection Agency (EPA); carbon capture and storage (CCS); liquefied natural gas (LNG); fossil fuels; green technologies; renewables